The Role of Small And Medium Enterprises (UKM) In Improving Employee Welfare According To A Sharia Economic Perspective (Study On UKM CV. Bakso Ikan Cahaya Bahari Lampung) - Febriyanto, Febriyanto; Ruslaini, Ruslaini; Sutopo, Heri (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
SMEs in Indonesia have an important role in economic development, especially in creating jobs and reducing unemployment. This research examines the role of UKM CV.Bakso Ikan Cahaya Bahari Lampung in improving employee welfare based on a sharia economic perspective. Welfare in Islam includes material and spiritual aspects, which are measured through decent wages, a comfortable working environment, and good relations between employees and management. This study uses a descriptive qualitative research method with semi-structured interviews with SME owners and managers. The research results show that these UKMs provide wages above the minimum wage, housing facilities, prayer rooms and food incentives, thereby helping to meet the basic needs of employees and their families. This UKM also implements a selective recruitment policy and provides a harmonious work environment. However, challenges such as managing employee loans are obstacles to improving welfare. Nevertheless, this UKM's commitment to sharia principles and employee welfare makes it a successful MSME model in providing positive social and economic impacts.